2018
DOI: 10.1002/ldr.2905
|View full text |Cite
|
Sign up to set email alerts
|

Functional metabolic diversity of the bacterial community in undisturbed resource island soils in the southern Sonoran Desert

Abstract: Resource islands (RIs), a natural revegetation phenomenon in arid lands, consist of a single nurse tree or few large shrubs and numerous understory nurslings. We analyzed 18 individual mesquite RIs for plant diversity and richness, area, trunk diameter (reflecting age), soil characteristics, physiological functionality of microbial populations, and interactions among these variables. Nursing Capacity reflected the availability of habitat and was positively correlated to plant richness, but not to plant diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 58 publications
0
7
1
Order By: Relevance
“…Saprophytic microbes have a wide range of functional abilities, and most soils contain most functional guilds of saprophytes (H€ attenschwiler et al 2005, Grau et al 2017, Semchenko et al 2018). For example, some ECMdominated ecosystems (e.g., boreal and tropical monodominant forests) tend to have low plant diversity despite the high richness in these fungal communities (McGuire 2007, Corrales et al 2016, Garcia et al 2018. Contrary to our expectation, a weak plant-mycorrhizal fungal (AMF and ECMF) correlation was observed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Saprophytic microbes have a wide range of functional abilities, and most soils contain most functional guilds of saprophytes (H€ attenschwiler et al 2005, Grau et al 2017, Semchenko et al 2018). For example, some ECMdominated ecosystems (e.g., boreal and tropical monodominant forests) tend to have low plant diversity despite the high richness in these fungal communities (McGuire 2007, Corrales et al 2016, Garcia et al 2018. Contrary to our expectation, a weak plant-mycorrhizal fungal (AMF and ECMF) correlation was observed.…”
Section: Discussioncontrasting
confidence: 99%
“…Such results indicate diverse plant community will not directly contribute to the mycorrhizal fungal diversity at the global scales, may be due to the mismatched host density and plant community diversity (Gilbert et al 2002, Cameron et al 2019. For example, some ECMdominated ecosystems (e.g., boreal and tropical monodominant forests) tend to have low plant diversity despite the high richness in these fungal communities (McGuire 2007, Corrales et al 2016, Garcia et al 2018). Moreover, it was reported that host plant genus-level diversity might be a better predictor of the ECMF diversity (Gao et al 2013), whereas most studies examined the overall plant community correlations with ECMF (Peay et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Lower numbers of CFUs for CM nutrient medium could be explained by lack of vegetation coverage at the sampling site and, as a result, the rareness of plant origin carbon sources (such as starch and sucrose in CM medium) in the soil in situ [39]. In addition, these compounds require preliminary hydrolysis for further assimilation by the cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, bacterial communities confined to areas of the desert lacking vegetation showed active assimilation of amino acids, amines, amides, and various polymers. In addition, representatives of Sinorhizobium, Bacillus, and Sphingomonas genera were isolated and identified in culture grown on selective medium for nitrogen-fixing bacteria [39].…”
Section: Introductionmentioning
confidence: 99%
“…Revegetation efforts generally result in improvement of soil fertility and enhancement of ecosystem services and functions such as carbon sequestration (Gao, Dang, Zhao, Liu, & Liu, 2018), nutrient cycling (Barliza, Peláez, & Campo, 2018;Hu et al, 2018), and soil microbial diversity and activity (Garcia et al, 2018;Liu et al, 2019); nevertheless, it can also lead to adverse effects such as salinity which may affect the success of restoration efforts in the long term (Yu & Wang, 2018) and generally increases plant productivity and carbon sequestration in the medium or long-term, as highlighted by Valdecantos and Fuentes (2018). Also in this issue, Luna, Vignozzi, Miralles, and Solé-Benet (2018) show that woodchip mulch can be effective for trapping runoff and sediment in mine rehabilitation sites, whereas organic amendments formed by composted waste can improve infiltration and reduce water erosion (Figure 2).…”
mentioning
confidence: 99%